Carcinofauna of the Santos-São Vicente bay-estuary Complex and Bertioga channel, especially Decapoda of Santos Bay, São Paulo, Brazil (Research, Society and Development, 2021)
Despite the geo-economic relevance of the Santos Bay, studies on the composition of its carcinofauna are still incipient. Thus, this study provides information on the crustacean fauna of the Santos Bay, also compiling data for the Santos-São Vicente Bay-Estuary Complex and the Bertioga Canal (CBESSB), located on the central coast of the state of São Paulo. Four sampling campaigns were carried out between April and December 2017 at six different points, using a shrimp boat type with standardized capture effort. A survey of species registered with CBESSB was also carried out. In total, 102 species were registered, belonging to 67 genera, 31 families, seven infraordens and three orders. The monitoring recorded a total of 13,404 specimens (91,890.07 g), belonging to 18 species, 15 genera, 11 families, four infraordens and one order. The species with the highest numerical abundance and weight were Xiphopenaeus kroyeri, Callinectes danae and Callinectes ornatus. In winter, the medium depth strip and the west side of the Santos Bay presented the greatest abundance. Despite the anthropization, CBESSB has a high richness of crustaceans and it is suggested that it be constantly monitored in order to support conservation and management measures, due to its high ecological, economic and social importance for the entire region of the central coast of the state of São Paulo.